Combined Vascular Resection for Locally Advanced Perihilar Cholangiocarcinoma. Issue 2 (February 2022) - Mizuno, Takashi; Ebata, Tomoki; Yokoyama, Yukihiro; Igami, Tsuyoshi; Yamaguchi, Junpei; Onoe, Shunsuke; Watanabe, Nobuyuki; Kamei, Yuzuru; Nagino, Masato
Abstract : Objective: To evaluate the efficacy and safety of combined vascular resection (VR) in advanced perihilar cholangiocarcinoma (PHC). Summary of Background Data: Hepatectomy combined with portal vein resection (PVR) and/or hepatic artery resection (HAR) is technically demanding but an option only for tumor eradication against PHC involving the hilar hepatic inflow vessels; however, its efficacy and safety have not been well evaluated. Methods: Patients diagnosed with PHC during 2001–2018 were included. Patients who underwent resection were divided according to combined VR. Patients undergoing VR were subdivided according to type of VR. Postoperative outcomes and OS were compared between patient groups. Results: Among the 1055 consecutive patients, 787 (75%) underwent resection (without VR: n = 484, PVR: n = 157, HAR: n = 146). The incidences of postoperative complications and mortality were 49% (without VR vs with VR, 48% vs 50%; P = 0.715) and 2.1% (without VR vs with VR, 1.2% vs 3.6%; P = 0.040), respectively. The OS of patients who underwent resection with VR (median, 30 months) was shorter than that of those who underwent resection without VR (median, 61 months; P < 0.0001); however, it was longer than that of those who did not undergo resection (median, 10 months; P < 0.0001). OS was not significantly different between those who underwent PVR and those who underwent HAR (median, 29 months vs 34 months; P = 0.517). Conclusion: VR salvages a large number of patients from having locally advanced PHC that is otherwise unresectable and is recommended if the hilar hepatic inflow vessels are reconstructable, providing acceptable surgical outcomes and substantial survival benefits. Abstract : Supplemental Digital Content is available in the text